2019
DOI: 10.3390/w11122572
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gate Operation in Reducing Problems with Cohesive and Non-Cohesive Sediments in Irrigation Canals

Abstract: Sediments cause serious problems in irrigation systems, adversely affecting canal performance, driving up maintenance costs and, in extreme cases, threatening system sustainability. Multiple studies were done on the deposition of non-cohesive sediment and implications for canal design, the use of canal operation in handling sedimentation problems is relatively under-studied, particularly for cohesive sediments. In this manuscript, several scenarios regarding weirs and gate operation were tested, using the Delf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Operations and maintenance aspects, particularly operating gates, also were found to affect sediment transport. The current study is consistent with evidence from previous observations (e.g., (Depeweg and Paudel, 2003;Munir, 2011;Osman et al, 2016;Paudel, 2010;Theol et al, 2019b). Arata-Chufa, for example, was designed with two gates at DB 1, where the main canal divides, forming a T-shape.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Operations and maintenance aspects, particularly operating gates, also were found to affect sediment transport. The current study is consistent with evidence from previous observations (e.g., (Depeweg and Paudel, 2003;Munir, 2011;Osman et al, 2016;Paudel, 2010;Theol et al, 2019b). Arata-Chufa, for example, was designed with two gates at DB 1, where the main canal divides, forming a T-shape.…”
Section: Discussionsupporting
confidence: 91%
“…To reduce the sedimentation problem, farmers use their indigenous knowledge to avoid withdrawal of water during times of high sediment concentration (beginning of the cropping season) and deflect surface runoff to prevent its entrance into the main canal. This tacit operation of the irrigation scheme by the farmers to reduce sediment deposition load is similar to the suggestion by previous studies (Depeweg and Paudel, 2003;Munir, 2011;Osman et al, 2016;Paudel, 2010;Theol et al, 2019b). However, the principal difference between the suggestion of these studies and that of farmers' practice is that the suggestion of these studies only is helpful to reduce sediment deposition that comes from the river source.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From these studies, it is clear that canal operation and the operating method have an effect on sediment transport. Theol et al [8] found that proper location of weirs and proper adjusting of the branch canal's gate can substantially reduce sedimentation problems while ensuring sufficient water delivery to crops.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The direction of the bedload transport is in first order equal to the direction of the depth-averaged velocity in a 2D simulation and equal to the direction of the velocity at the reference height (a) in a 3D simulation [38]; secondary flow correction is applied in 2D simulations, and adjustments due to bed slope are applied in both 2D and 3D simulations. Running the model in 2D mode is to ensure better representation of the sediment processes and the large scale behavior with an acceptable simulation time period [8]. Running the model in 3D mode (5 layers) provides information about flow and sediment parameters in the vertical direction and gives more details near structures [39].…”
Section: Governing Equationsmentioning
confidence: 99%